The value of the integrative approach in tardigrade taxonomy: the case study of an Antarctic eutardigrade. - BERTOLANI, Roberto; CESARI, Michele; VECCHI, MATTEO; REBECCHI, Lorena; GUIDETTI, Roberto (Grifo, 2014)
The use of the molecular approach in tardigrades has recently widespread for identifying taxa and evolutionary lineages. Firstly, it has been utilized for identifying the phylum position within Ecdysozoa and then to recognize both its evolutionary lineages and species. As regards phylogeny, in several cases a good correspondence between molecular and morphological data was found, but in others results were contrasting. For example, the Eutardigrada genera Hypsibius and Isohypsibius, which have two different types of claws sharing asymmetry with respect to the median plane of the leg, were considered belonging to the same subfamily, and 50 years ago subgenera of the same genus, Hypsibius. Molecular data have pointed out that these two genera belong to different superfamilies (Hypsibioidea and Isohypsibioidea). Other genera were attributed to one or the other superfamily according to the morphology of their claws, attributions always confirmed when molecular support was obtained. In Antarctica we found tardigrades with claws attributable to Ramajendas (Isohypsibioidea, Isohypsibiidae) for the particular length of the main branch of the external claw and its weak connection to the basal tract. Ramajendas is only from Antarctica and surrounding austral areas. We also found other specimens, belonging to Ramazzottius and Hebesuncus (Hypsibioidea, Ramazzottiidae). This material allowed us to carry out an integrative approach, obtaining both molecular data (18S and 28S genes) and new morphological information. Both Bayesian and maximum likelihood cladograms clearly placed the specimens with putative Ramajendas claws together with Hebesuncus and Ramazzottius, within the Ramazzottiidae family. New morphological data on the specimens with putative Ramajendas claws evidenced that, like in Ramazzottius, there are two elliptical structures on the head and the eggs are ornamented and laid freely (on the contrary, in all Isohypsibioidea the eggs are smooth shelled and laid within the exuvium). Therefore, both approaches ...